2007
DOI: 10.2337/dc06-2056
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Identification of Urinary Biomarkers of Diabetic Nephropathy

Abstract: OBJECTIVE -Diabetic nephropathy is a serious complication of both type 1 and type 2 diabetes, and, unless arrested, leads to end-stage renal disease. Current diagnosis consists of urine assays of microalbuminuria, which have inadequate specificity and sensitivity.RESEARCH DESIGN AND METHODS -We used proteomic analyses to identify novel biomarkers of nephropathy in urine from type 2 diabetic patients with demonstrated normo-, micro-, or macroalbuminuria. Samples were analyzed by fluorescence two-dimensional (2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
123
1
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(135 citation statements)
references
References 33 publications
9
123
1
2
Order By: Relevance
“…In three independent proteomics scans, ␣ 1 -antitrypsin, a serine protease inhibitor, was present at higher levels in urine and renal tissue of patients with diabetic nephropathy compared with controls (22)(23)(24). Higher levels of ␣ 1B -glycoprotein have also been reported previously in urine of patients with proteinuric diabetic nephropathy compared with normoalbuminuric diabetics (25).…”
Section: Optimizing Proteomics Platform For Urine Biomarker Discoverysupporting
confidence: 52%
“…In three independent proteomics scans, ␣ 1 -antitrypsin, a serine protease inhibitor, was present at higher levels in urine and renal tissue of patients with diabetic nephropathy compared with controls (22)(23)(24). Higher levels of ␣ 1B -glycoprotein have also been reported previously in urine of patients with proteinuric diabetic nephropathy compared with normoalbuminuric diabetics (25).…”
Section: Optimizing Proteomics Platform For Urine Biomarker Discoverysupporting
confidence: 52%
“…By 2-DE, we found that all children with HIVAN and HIV-HUS showed high urinary levels of these 11 proteins, when compared with samples harvested from HIV-infected children without renal disease, and to the normal values reported in other studies for HIV-negative controls (17)(18)(19)(20)(21)(22)(23)(24). These proteins are: orosomucoid, transferrin, ␣-1-microglobulin, zinc ␣-2-glycoprotein, ␣-1-antitrypsin, complement factor B, haptoglobin, transthyretin, RBP, albumin, and hemopexin ( Figure 1 and Table 1).…”
Section: Proteomicsmentioning
confidence: 58%
“…Ceruloplasmin and prostaglandin-H2 D-isomerase were found to be differentially expressed in type 2 diabetic patients with nephropathy; however, the results from separate studies did not agree. In a two-dimensional Difference Gel Electrophoresis (DIGE) study, Paturi et al (22) reported that ceruloplasmin decreased in diabetic patients with normoalbuminuria, and that prostaglandin-H2 D-isomerase decreased in diabetic patients with macroalbuminuria, compared with healthy controls. However, Narita et al (23) and Jiang et al (24) observed increases in these proteins using an immunoradiometric assay and two-dimensional DIGE method, respectively.…”
Section: Resultsmentioning
confidence: 99%